Pengaruh Implementasi Green Accounting, Material Flow Cost Accounting Dan Environmental Performance Terhadap Sustainable Development - Siska Purnamalita May; Irfan Zamzam; Rinto Syahdan; Zainuddin Zainuddin (Politeknik Ganesha Medan, 2023)
The role of companies engaged in the plantation industry and palm oil processing has a very important effect on the world, especially Indonesia. The existence of palm oil companies can help the world in increasing food needs, increasing job opportunities, and helping to increase Indonesia's economic growth. The development of palm oil companies is very fast every year, this makes companies have to pay more attention to sustainable development, while maintaining stability to environmental, social and economic practices around the company to be maintained in the midst of increasing company development but there must always be a contribution so that the sustainability of the company is maintained for the future. Therefore, the purpose of this study is to analyze the effect of the application of green accounting, material flow cost accounting and environmental performance on sustainable development in palm oil companies listed on the IDX from 2017-2021. The data collection method uses purposive sampling. There were 15 palm oil companies that met the criteria as a sample, bringing the research data to 72. The technique used in this study is the Structural Equation Model (SEM) analysis technique. The software used is SmartPLS 3. The results showed that green accounting has no effect on sustainable development. MFCA has a positive and significant influence on sustainable development. Meanwhile, environmental performance has no effect on sustainable development